KYANITE FROM THE WESTERN PART OF THE SØR RONDANE MOUNTAINS, EAST ANTARCTICA - アサミ, マサオ; シライシ, カズユキ; ASAMI, Masao; SHIRAISHI, Kazuyuki (National Institute of Polar Research, 1987)
P(論文) Kyanite was found in a granulite-facies pelitic gneiss from the western part of the Sor Rondane Mountains. Kyanite, accompanied by some quartz and muscovite, occurs restrictedly in biotite aggregates (Type-B biotite) by which garnet porphyroblasts are often embayed and fringed, and thus is isolated from the matrix consisting of sillimanite, tabular biotite (Type-A biotite), K-feldspar, plagioclase, quartz, ilmenite, rutile and spinel, which contacts with no quartz. The embayed garnet characteristically shows an outward X_<Fe>-increase near the embayed edge and has magnesian interior, whereas the non-embayed garnet, which is idiomorphic to hypidiomorphic and surrounded by the matrix minerals, is actually unzoned with compositions as magnesian as the former garnet interior. On the basis of the textural and paragenetic relations, it is inferred that this rock was recrystallized at two stages of metamorphism and that kyanite was formed in association with Type-B biotite, Fe-rich garnet (embayed edge), some quartz and muscovite through the retrograde reaction : garnet+K-feldspar+H_2O=kyanite+biotite+quartz. Compositions of garnet, biotite and plagioclase in addition to the mineral assemblages of the two stages suggest that the granulite-facies metamorphism has taken place at about 830℃ and 8kb followed by the kyanite-forming retrograde event under conditions of about 560℃ and at least 4.5kb. departmental bulletin paper